2013
DOI: 10.1111/ijtd.12017
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of transfer of training for service quality and job satisfaction: an empirical study in the Malaysian public sector

Abstract: The significance of transfer of training to organizations has been acknowledged by many studies. However, the consequences of transfer of training, particularly for employees, have still not been adequately explored. The present study was conducted to address this gap. Specifically, it explores the relationship among transfer of training, service quality and job satisfaction. Data for this study were collected through surveys of employees, their supervisors and their colleagues. Data were analysed using struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
25
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 73 publications
9
25
0
2
Order By: Relevance
“…A recent study shows that POS has a positive impact on transfer of training (Zumrah et al, 2012). There was also one study which indicated that transfer of training was positively related to service quality (Zumrah et al, 2013). Based on both findings, this study argues that transfer of training could mediate the relationship between POS and service quality.…”
Section: Malaysian Public Sectormentioning
confidence: 62%
“…A recent study shows that POS has a positive impact on transfer of training (Zumrah et al, 2012). There was also one study which indicated that transfer of training was positively related to service quality (Zumrah et al, 2013). Based on both findings, this study argues that transfer of training could mediate the relationship between POS and service quality.…”
Section: Malaysian Public Sectormentioning
confidence: 62%
“…Referring to Fang and Zhang (2014), innovative education is measured with learning commitment, vision sharing, and open mind in this study. Zumrah et al (2013) pointed out "innovation" as the adoption of a new idea and behavior. From resource-based theory, innovation is defined as changing the output of resources that innovation capability is a new idea for internal facilities, systems, policies, procedures, products, and services of an enterprise (Guta, 2013).…”
Section: Innovative Educationmentioning
confidence: 99%
“…highly positive effects of innovation capability on organizational performance. Zumrah et al (2013) pointed out the positive effect of organization innovation on performance, and even the directly positive effects of technology innovation and management innovation on organizational performance. Seppälä et al (2015) considered that the effect of management innovation on organizational performance was larger than the effect of technology innovation on organizational performance.…”
Section: Research On Innovation Capability and Organizational Performmentioning
confidence: 99%
“…Guthrie et al (2012) described it as a psychological state which involved not only the consistent value between individual and organization, but was also influenced by organizational loyalty, and the desire, needs, or obligation. Zumrah et al (2013) mentioned organizational commitment as an attitudinal concept that an individual strongly agreed with the goal and value of the organization and involved such perceived goal and value in the role in the organization.…”
Section: Organizational Commitmentmentioning
confidence: 99%